Bio-Inspired Control of an Arm Exoskeleton Joint with Active-Compliant Actuation System. Issue 2 (22nd July 2009) - Folgheraiter, Michele; de Gea, Jose; Bongardt, Bertold; Albiez, Jan; Kirchner, Frank
Abstract : This paper presents the methodology followed on the design of a multi-contact point haptic interface that uses a bio-inspired control approach and a novel actuation system. The combination of these components aims at creating a system that increases the operability of the target, and, at the same time, enables an intuitive and safe tele-operation of any complex robotic system of any given morphology. The novelty lies on the combination of a thoughtful kinematic structure driven by an active-compliant actuation system and a bio-inspired paradigm for its regulation. Due to the proposed actuation approach, the final system will achieve the condition of wearable system. On that final solution, each joint will be able to change its stiffness depending on the task to be executed, and on the anatomical features of each individual. Moreover, the system provides a variety of safety mechanisms at different levels to prevent causing any harm to the operator. In future, the system should allow the complete virtual immersion of the user within the working scenario.